AGAMA DAN KORUPSI: Kajian Etika Sosial dan Religiusitas dalam Konteks Pembangunan Nasional - Abdul Kholiq Zahron; Yusuf Zinal Abidin; Aep Kusnawan; Muhamad Zuldin (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
Indonesia is known as a country with a high level of religiosity. Nearly every aspect of social life is imbued with religious practices. However, a paradox arises when corruption rates remain high and national development often stalls. This paper examines the relationship between religion, corruption, and development. Using a descriptive qualitative approach, it was found that high levels of religiosity do not automatically equate to low levels of corruption. This is due to the weak internalization of religious values ​​in social life, the dominance of ritualistic understanding of religion, and the limited role of religious leaders in overseeing development. Therefore, a reorientation of religious understanding toward a more ethical, transformative, and practical one is urgently needed to realize just and integrated development.